STRATEGIES FOR INCREASING THE COMPETITIVENESS OF MICRO SMALL AND MEDIUM ENTERPRISES (MSMEs) IN BANYUMAS DURING THE COVID-19 PANDEMIC - Mastur Mujib Ikhsani; Selamet Eko Budi Santoso; Fatmah Bagis; Arini Hidayah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
MSMEs have become the backbone and buffer zone that saves the country from the economic downturn. However, the current COVID-19 pandemic has left many MSMEs helpless. One by one they fell quickly. They lost their market due to the weakening of people's purchasing power due to the decline in economic activity during large-scale social restrictions in a number of areas. The impact of this pandemic was also felt by Banyumas Regency, whose MSMEs were also affected. So that a strategy to increase the competitiveness of MSMEs in Banyumas is needed to survive during the covid-19 pandemic. The purpose of this study is to find out strategies to increase the competitiveness of SMEs. Knowing the strengths, weaknesses, opportunities, and threats of SMEs. Knowing the problems in MSMEs and strategies to increase MSME competitiveness to achieve high competitiveness. This study uses descriptive methods and SWOT analysis to obtain a strategy to increase the competitiveness of MSMEs during the covid-19 pandemic. MSMEs in Banyumas Regency is located in square I, meaning that in this position MSMEs in Banyumas Regency are very supportive of aggressive growth strategies to gain company advantages in order to compete with other business entities. Keywords: MSMEs, Competitiveness, SWOT, Covid-19 pandemic